P10 A multicentre analysis of the management of gonorrhoea (GC). (18th May 2015) - Bakar, Mohd Sabri Abu; Crowe, Gail; Price, Huw; Ramogi, Malaki; Lechelt, Martin; Wallis, Emma; Jaleel, Henna
Abstract : Background: GC is the second most common sexually transmitted infections after chlamydia. The emergence of resistant strains has made it vital for each case to be managed according to national standards in order to reduce onward transmission. Aim: To compare the current management of GC across five centres in Essex in accordance with the British Association of Sexual Health and HIV (BASHH) auditable outcomes. Methods: 30 case notes of confirmed GC diagnosis from each centre between January–September 2013 were reviewed. Data collected included demographic, sites of infection, diagnostic methods, chlamydia testing, treatment protocol, test of cure (TOC), partner notification (PN) and health adviser (HA) referral. Results: As illustrated in Table 1. 150 cases were analysed. Most infections were acquired locally, diagnosed clinically alongside microscopy with majority isolated from the urethra in male and cervix in female. 3 resistant strains were identified. Multiple sites of infection were also observed. 143(95.0%) cases were managed in accordance with all treatment and diagnostic standards but only 84.6% had TOC, 83.8% PN and 67.7% seen a HA. Conclusion: Almost all GC cases in the region were well managed. However TOC, PN and HA referral standards were not met likely due to lack of resources and poor documentation.